Here's looking at you ([S.l.] : Open University Educational Enterprises, 1982)
Consists of scene from a Univ. faculty party, with a running commentary on the proceedings by two social psychologists. The documentary is based on the non-verbal aspects of social behaviour and is closely related to the ideas of the socialogist Erving Goffman.
Keywords: Collective behaviour; Social action; Action research